Growth orientation mechanism of TiO2 nanotubes fabricated by anodization. (12th February 2019) - Yin, Bo; Qian, Qun; Xiong, Zhongliang; Jiang, Hongyi; Lin, Yue; Feng, Daolun
Abstract: TiO2 nanotubes (TNTs) fabricated by anodization have been extensively researched in recent years. However, the mechanism that controls the growth orientation of anodic TNTs is still not clear. Here, we firstly examine their growth orientation systematically. Combined with the previous literature, the results of anodization on rotated Ti foil and thin Ti wire confirm that almost all of the TNTs grow vertically to the local Ti substrate surface. Their growth orientation predominantly depends on the local electric field around the bottom of the nanotube. The distribution of the local electric field is regulated by the shape of the initial nano-scale local Ti substrate surface (INLTSS). Most of the INLTSS is nearly flat, which leaves vertical, circular, and straight TNTs. In terms of the evolution of TNTs fabricated on a micron-scale convex surface, the vertical growth of TNTs leads to a continuous decrease in the oxide/substrate (O/S) interface area, and a few TNTs are periodically crushed and detached from the O/S interface. For a micron-scale concave surface, due to the ever-increasing O/S interface area, Y-branched TNTs occurred periodically as a response to avoid a vacancy on the oxide/substrate interface.